2014
DOI: 10.1530/joe-14-0147
|View full text |Cite
|
Sign up to set email alerts
|

Gender- and region-specific alterations in bone metabolism in Scarb1-null female mice

Abstract: A positive correlation between plasma levels of HDL and bone mass has been reported by epidemiological studies. As scavenger receptor class B, type I (SR-BI), the gene product of Scarb1, is known to regulate HDL metabolism, we recently characterized bone metabolism in Scarb1-null mice. These mice display high femoral bone mass associated with enhanced bone formation. As gender differences have been reported in HDL metabolism and SR-BI function, we investigated gender-specific bone alterations in Scarb1-null mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…We also found that there was a sex‐specific response to the loss of CD97 in terms of the bone phenotype. This was not surprising, as we and others have previously observed, in several gene‐inactivated KO models , that those animals exhibited a sex‐specific bone phenotype at the same age as examined herein. Female mice were found to exhibit alterations in the trabecular bone, while male mice showed cortical changes.…”
Section: Discussionsupporting
confidence: 88%
“…We also found that there was a sex‐specific response to the loss of CD97 in terms of the bone phenotype. This was not surprising, as we and others have previously observed, in several gene‐inactivated KO models , that those animals exhibited a sex‐specific bone phenotype at the same age as examined herein. Female mice were found to exhibit alterations in the trabecular bone, while male mice showed cortical changes.…”
Section: Discussionsupporting
confidence: 88%
“…( 7 ) HDL‐dependent regulation of caveolin gene expression in osteoblasts has also been proposed as an alternative explanation of the bone phenotype. ( 7 ) Martineau and colleagues, ( 33 ) on the other hand, have proposed that Scarb1 is not required for the suppression of bone marrow stromal cell number by OxLDL. However, in that study the investigators used much higher doses of a different OxLDL preparation than the one we used, and examined only cell number—not apoptosis or proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of these SRs in bone homeostasis has been studied only in mice that lack SRs globally, but the data from those studies are conflicting. Indeed, it has been reported that although mice with global deletion of CD36 have low bone mass 50 , mice with global deletion of SR-B1 maintained on a normal diet have high bone mass 27 , 51 , 52 , as well as striking architectural and histomorphometric similarities with E06-scFv transgenic mice. Be that as it may, the global nature of the deletion makes it difficult to understand the role of SR-B1 specifically in osteoblasts and does not rule out the possibility that the phenotype is due to effects of OSEs in other cell types.…”
Section: Discussionmentioning
confidence: 99%